Incisionless Otoplasty: Current State of the Art - Madsen Buba, Cibele; Gantous, Andres M. (Facial Plastic Surgery, 2024)
Prominent ears, also known as prominauris, inflict psychological distress and suffering on both children and adults. Otoplasty has become one of the most common aesthetic operations due to its high prevalence and significant impact on patients. Various surgical techniques for otoplasty have been documented and developed over time. While complications are rare, open and cartilage-resection techniques may result in hemorrhage, hematomas, contour deformities, hypertrophic scarring, and keloid formation. Incisionless otoplasty has been demonstrated in the literature to be an effective method, when correctly indicated, to correct prominauris with a shorter recovery time and reduced morbidity. A thorough preoperative evaluation, awareness of the different techniques, and assessment of their appropriate application minimize potential risks and unpleasant results.
Keywords: prominent ears; protruding ears; prominauris; otoplasty; incisionless otoplasty; percutaneous otoplasty